Pengaruh Pembayaran Dividen Terhadap Kinerja Keuangan Perusahaan Manufaktur - Reyka Nafara Hilsya; Noopya Lestari; Qoriana Dewi; Henny Setyo Lestari (Jurnal Ekonomi, 2022)
This The purpose of this study is to analyze the effect of Dividend Payment on Firm Financial Performance of manufacturing companies listed on the IDX for the 2016-2020 period. The dependent variable is firm financial performance, the independent variable in this study is Dividend Payout Ratio and Decision of Dividend Payment, and the control variable is ROA and Tobins'q. The number of samples in this study were 29 manufacturing companies. The sampling technique used is purposive sampling technique. The results of panel data regression show that the results of the Dividend Payout Ratio and Decision of Dividend Payment have a significant effect on firm financial performance, but the DPR and Decision of Dividend Payment have no effect on firm financial performance (tobins'q). The results showed that Dividend Payout Ratio and Decision of Dividend Payment had an influence on firm financial performance. Therefore, investors can provide input for companies to consider their decisions.